2016
DOI: 10.7196/samj.2016.v106i5.9952
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends of clinical trials performed in South Africa

Abstract: Background. Investigators and sponsors of clinical trials have an ethical obligation to disseminate clinical trial results, whether positive or negative, in a timely manner. Objectives. To determine the publication rate and average time to reporting for clinical trials carried out in South Africa (SA) and to explore factors indicating whether a study is published or not. Conclusion. The absence of complete outcomes data from SA clinical trials warrants utmost attention. The study puts forward a case to the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In South Africa, Physics is offered jointly with Chemistry under the discipline Physical Science for high school learners between grades 10 and 12. Over the years, the pass rate and quality of the grade 12 final matriculation results in Physical Science has been poor [3], [4]. The study in [5] confirms that one of the main reasons for poor performance in Physical Science is that a significant number of teachers may not have specialized in teaching both Physics and Chemistry, and in this particular study, most of the teachers were not competent to teach Physics at the required level.…”
Section: Introductionmentioning
confidence: 52%
“…In South Africa, Physics is offered jointly with Chemistry under the discipline Physical Science for high school learners between grades 10 and 12. Over the years, the pass rate and quality of the grade 12 final matriculation results in Physical Science has been poor [3], [4]. The study in [5] confirms that one of the main reasons for poor performance in Physical Science is that a significant number of teachers may not have specialized in teaching both Physics and Chemistry, and in this particular study, most of the teachers were not competent to teach Physics at the required level.…”
Section: Introductionmentioning
confidence: 52%
“…In contrast, more than half of those in the ISRCTN were reported. While there is limited literature on this important trend in SSA generally, a study found that about 48.6% of completed trials in the South African National Clinical Trials Register (SANCTR) were registered within a median time of 2 years of completion and the majority of the published trials were those with a positive outcome [22], revealing the possibility of publication bias. Our study relied solely on completed trials with results available in the study field and did not further verify if these studies have been INGO international non-governmental organisations; this will not equal total completed trials because sponsor type was obtained by extracting the common theme from a free text, indicating the possibility of a double count published in peer-reviewed journals as was done in the South African study.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage of publication is higher compared with the CTs registered at ClinicalTrials.gov (46%) and those registered at the South African Registry of Clinical Trials (49%). 6,25 In contrast, CTs registered with the National Institute of Health from the United States and Norway have a higher proportion of CTs published (93% and 71%, respectively). 23,31 The percentage of published CTs is a good indicator of monitoring national or regional registries.…”
Section: Cts Published and Registered In The Repecmentioning
confidence: 99%
“…We used an ad hoc methodology based on previous papers about CTs' publication. [23][24][25] Briefly, we reviewed Medline/PubMed, Scopus, and Google Scholar using a combination of the following entry terms: "Responsible author last name," "Intervention," "NCT number," and "Applicant institution." We performed a double-check using matching criteria between identified reference and CT. For this process, we took in account the study aim, design, type of intervention, sample size, and the number of sites.…”
Section: Publication Assessmentmentioning
confidence: 99%
See 1 more Smart Citation